Vertical relations and number of channels in quality-differentiated markets - Emanuele Bacchiega; Olivier Bonroy (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Double marginalization causes inefficiencies in vertical markets. This paper argues that such inefficiencies may be beneficial to final consumers in markets producing vertically differentiated goods. The rationale behind this result is that enhancing efficiency in high-quality supply chains through vertical integration may drive out of the market low-quality ones, thus affecting market structure. As a consequence, restoring-efficiency vertical integration may reduce consumer surplus, even in the absence of foreclosure strategies by the newly integrated firms. From a policy standpoint, our paper suggests that input and/or customer foreclosure should not be considered as the only source of antitrust concern when assessing the effects of vertical integration.
Keywords: L13; L22; L4; 330